Analisis Historiografi Kitab Hadis al-Arba’in; Studi atas Karya Muhammad Mahfuz al-Tarmasi dan Hasyim Asy’ari - Syamsul Ma'arif Ilyas; Muh Rizaldi (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2023)
This paper intends to examine the comparative analysis of the historiography of the hadith book al-Arba'in; al-Minhah al-Khairiyyah by Muhammad Mahfuz al-Tarmasi and the book al-Arba'ina Hadisan Ta'allaqu bi Mubadi Jami'iyah Nahdiyatul Ulama by Hasyim Asy'ari. Departing from the assumption that, these two figures were born from the same sociocultural and scientific style so that there is a possibility of similarities and differences that are interesting to study, especially in terms of scientific transmission both have a teacher-student relationship. Therefore, there are two questions raised in this article. (1) What is the historiography of the writing of Mahfuz al-Tarmasi's al-Arba'in and Hasyim Asy'ari's al-Arba'in. (2)How is the comparison between Mahfuz al-Tarmasi's al-Arba'in and Hasyim Asy'ari's al-Arba'in. In answering that question, the author uses a historical approach; starting from heuristics (collecting sources), verification, interpretation and then historiography. This study concludes that, first, these two books were not written in an empty space, they were formed from sociocultural constructs (patterns of religion, culture, tradition, politics, thought) of the late 19th century and early 20th century. Secondly, the teacher-student relationship between Mahfuz Tarmasi and Hasyim Asy'ari became the starting point for the similarities and differences (to say not identical) which are clearly visible from two aspects, namely the history of the writing of the book and the systematic preparation of the book.